Analysis Of The Use Of Genting Kalianak Urban Village Funds For Handling Waterlogging Through The Development Of Facilities And Infrastructure In The City Of Surabaya - Alfina Audry Anggraeni; Susi Hardjati (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study analyses the use of urban village funds in the city of Surabaya to combat flooding through the development of infrastructure such as drainage, infiltration ponds and water pumps. The results show that the programme has had positive impacts, including reducing flooding, improving people's quality of life, and strengthening economic competitiveness. However, the success of the programme still faces challenges such as budget constraints, sub-optimal coordination and low community participation. To improve the effectiveness of the programme, it is necessary to strengthen fund management, community education and a better monitoring system so that the programme can contribute to the development of a resilient and sustainable city. Keywords: Urban Village Funds, Waterlogging, Infrastructure, Surabaya, Community Participation.